2022
DOI: 10.1029/2021gl096498
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Observed Recent Decrease in Low Clouds Over the Northeastern Pacific to Cloud‐Controlling Factors

Abstract: Marine low clouds cool the Earth's climate, with their coverage (LCC) being controlled by their environment. Here, an observed significant decrease of LCC in the northeastern Pacific over the past two decades is linked quantitatively to changes in cloud‐controlling factors. In a comparison of different statistical and machine learning methods, a decrease in the inversion strength and near‐surface winds, and an increase in sea surface temperatures (SSTs) are unanimously shown to be the main causes of the LCC de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This effect seems to be more pronounced in situations with a lower amount of cloud droplets. Higher SST conditions are associated with increased surface fluxes, a deeper and less stable marine boundary layer, and an increased moisture difference between the marine boundary layer and the troposphere [68,69]. In these conditions, the evaporation-entrainment process may be facilitated [40], leading to a less positive N d -LWP relationship.…”
Section: Resultsmentioning
confidence: 99%
“…This effect seems to be more pronounced in situations with a lower amount of cloud droplets. Higher SST conditions are associated with increased surface fluxes, a deeper and less stable marine boundary layer, and an increased moisture difference between the marine boundary layer and the troposphere [68,69]. In these conditions, the evaporation-entrainment process may be facilitated [40], leading to a less positive N d -LWP relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Spatial trends (Fig. S9b-c) clearly show Sc declines in the northeast Pacific (Andersen, Cermak, Zipfel, & Myers, 2022;Loeb, Thorsen, Norris, Wang, & Su, 2018;Stephens et al, 2022), but also show substantial trends of decreasing cloud fraction in the southeast Atlantic and increasing cloud fraction in the southeast Pacific and northeast Atlantic. Sc albedo has been decreasing in almost all regions, with particularly strong trends off the western coasts of North America and southern Africa (Fig.…”
Section: Trendsmentioning
confidence: 89%
“…Cao et al (2021) replaced CTRC with RH and showed that these primary cloud-controlling parameters explained up to 97% of the variability in Cf over the United States East Coast. In this study, we further introduce SST as a controlling parameter of cloud coverage due to its domination of Cf (Andersen et al, 2022).…”
Section: Methodsmentioning
confidence: 99%